Psychoanalysis, Classic Social Psychology and Moral Living let the conversation begin - Marcus, Paul 1953- (Routledge, 2020)
In Psychoanalysis, Classic Social Psychology and Moral Living: Let the Conversation Begin, Paul Marcus uniquely draws on psychoanalysis and social psychology to examine what affects the ethical decisions people make in their everyday life. Psychoanalysis traditionally looks at early experiences, concepts and drives which shape how we choose to behave in later life. In contrast, classic social psychology experiments have illustrated how specific situational forces can shape our moral behaviour. In this ground-breaking fusion of psychoanalysis and social psychology, Marcus gives a fresh new perspective to this and demonstrates how, in significant instances, these experimental findings contradict many presumed psychoanalytic ideas and explanations surrounding psychoanalytic moral psychology. Examining classic social psychology experiments, such as Asch's line judgement studies, Latan and Darley's bystander studies, Milgram's obedience studies, Mischel's Marshmallow Experiment and Zimbardo's Stanford Prison Experiment, Marcus pulls together insights and understanding from both disciplines, as well as ethics, to begin a conversation and set out a new understanding of how internal and external factors interact to shape our moral decisions and behaviours. Marcus has an international reputation for pushing boundaries of psychoanalytic thinking and, with ethics being an increasingly relevant topic in psychoanalysis and our world, this pioneering work is essential reading for psychoanalysts, psychoanalytic psychotherapists, moral philosophy scholars and social psychologists